Pengendalian Persediaan Bahan Baku dengan Metode MRP Guna Mencapai Efisiensi Biaya Persediaan Pada UMKM Kerupuk Puli - M Jakariya; Nurhamidah Nurhamidah (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The main problem faced by MSMEs is the mismatch between production schedules and demand fluctuations, which often cause raw material stock shortages and lead to wasted production costs. Quantitative data such as production records, demand levels, and various inventory costs are then analyzed using the MRP approach to determine raw material requirements, prepare production schedules, and find the lowest total costs. The results of the analysis show that the LFL method provides the lowest total inventory cost, which is Rp40,365,400. This figure is much more efficient than the EOQ method (Rp83,922,260), POQ (Rp65,873,280), and the actual costs incurred by the company (Rp70,575,000). Based on these findings, this study recommends the use of the LFL method to reduce storage costs, prevent overstocking, and improve accuracy in meeting market demand. Practically, the results of this study provide a tangible contribution to MRP-based inventory management, particularly for MSMEs with similar characteristics.